Taxocene of pelagic copepods in coastal waters of the Argentine Islands, West coast of the Antarctic Peninsula, in 2021—2022 - Tkachenko, V. (Ukrainian Antarctic Journal, 2022)
Pelagic ecosystems are changing in response to the recent climate warming. The mesozooplankton and copepods in particular are important indicators of the state of aquatic ecosystems. Zooplankton in Antarctic waters has been monitored regularly to study biodiversity, food chains, and ecological cycles. In 2021–2022, pilot study of mesozooplankton groups was added to the marine biological research of the Ukrainian Antarctic Program. The preliminary information was obtained on the taxonomic composition and functional characteristics of the taxocene of copepods in the coastal waters of the Argentine Islands. The observed diversity is strongly influenced by the conditions and the available sampling gear. The samples were collected from motor boats using three kinds of plankton nets depending on the weather and ice conditions. From June to February, the predominant species were the common coastal species and species adapted to feeding in the cold upper layers in winter. Trawling samples collected from March to late May best illustrate the seasonal dynamics of the mesozooplankton communities’ temporary and permanent components. Twelve copepods from eight families were identified to the species level. Most constituent species were omnivorous (7 species), followed by detritophages (3 species). The community’s phytophages and predators were locally common. This trophic distribution likely is evidence that they were collected in the surface layer, which is not always favorable for feeding. Therefore, the percentage of omnivorous opportunists was relatively high. Some of the sampled material requires molecular-biological analysis, especially the copepods from the Oncaea Philippi, 1843 and Triconia Böttger-Schnack, 1999 genera. The older copepodites, in particular the adult specimens, were rarely collected. The state of the material was not ideal for unambiguous identification by morphological features. Comparing the results with the latest research on the west coast of the Antarctic Peninsula, we see that the species composition is highly similar (around 80%), except for the deep-water taxa.